Step
*
2
of Lemma
bag-append-no-repeats
1. T : Type
2. as : bag(T)
3. bs : bag(T)
4. bag-no-repeats(T;as + bs)
⊢ bag-no-repeats(T;as) ∧ bag-no-repeats(T;bs) ∧ (∀z:T. (z ↓∈ as 
⇒ (¬z ↓∈ bs)))
BY
{ (Auto THEN ((BagToList 2 THEN Auto) THEN BagToList 3 THEN Auto)⋅) }
1
1. T : Type
2. as : T List
3. bs : T List
4. bag-no-repeats(T;as + bs)
⊢ bag-no-repeats(T;as)
2
1. T : Type
2. as : T List
3. bs : T List
4. bag-no-repeats(T;as + bs)
5. bag-no-repeats(T;as)
⊢ bag-no-repeats(T;bs)
3
1. T : Type
2. as : T List
3. bs : T List
4. bag-no-repeats(T;as + bs)
5. bag-no-repeats(T;as)
6. bag-no-repeats(T;bs)
7. z : T
8. z ↓∈ as
⊢ ¬z ↓∈ bs
Latex:
Latex:
1.  T  :  Type
2.  as  :  bag(T)
3.  bs  :  bag(T)
4.  bag-no-repeats(T;as  +  bs)
\mvdash{}  bag-no-repeats(T;as)  \mwedge{}  bag-no-repeats(T;bs)  \mwedge{}  (\mforall{}z:T.  (z  \mdownarrow{}\mmember{}  as  {}\mRightarrow{}  (\mneg{}z  \mdownarrow{}\mmember{}  bs)))
By
Latex:
(Auto  THEN  ((BagToList  2  THEN  Auto)  THEN  BagToList  3  THEN  Auto)\mcdot{})
Home
Index